2016
DOI: 10.1080/17470218.2015.1018282
|View full text |Cite
|
Sign up to set email alerts
|

I “hear” what you're “saying”: Auditory perceptual simulation, reading speed, and reading comprehension

Abstract: Auditory perceptual simulation (APS) during silent reading refers to situations in which the reader actively simulates the voice of a character or other person depicted in a text. In three eye-tracking experiments, APS effects were investigated as people read utterances attributed to a native English speaker, a non-native English speaker, or no speaker at all. APS effects were measured via online eye movements and offline comprehension probes. Results demonstrated that inducing APS during silent reading result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 79 publications
(116 reference statements)
0
17
1
Order By: Relevance
“…The results suggest that readers rely on a word-order heuristic as well as a plausibility heuristic, which conspire to cause miscomprehension. The same processing pattern has been observed in second language (L2) English speakers' comprehension as well (Jacob & Felser, 2016;Lim & Christianson, 2013a).Recently, Zhou and Christianson (2016a) found that readers engage in good-enough processing when reading unambiguous RCs with similarly competing syntactic and semantic information. Computation of the more challenging ORC structure in (3a) is interfered by the implausible semantic information, causing longer fixation durations, longer whole sentence reading times, more regressions in sentence processing, and lower comprehension accuracy in a paraphrase verification task (3b).…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…The results suggest that readers rely on a word-order heuristic as well as a plausibility heuristic, which conspire to cause miscomprehension. The same processing pattern has been observed in second language (L2) English speakers' comprehension as well (Jacob & Felser, 2016;Lim & Christianson, 2013a).Recently, Zhou and Christianson (2016a) found that readers engage in good-enough processing when reading unambiguous RCs with similarly competing syntactic and semantic information. Computation of the more challenging ORC structure in (3a) is interfered by the implausible semantic information, causing longer fixation durations, longer whole sentence reading times, more regressions in sentence processing, and lower comprehension accuracy in a paraphrase verification task (3b).…”
mentioning
confidence: 56%
“…As a result, implausible sentences are more likely to end up misinterpreted with their thematic roles reversed, thereby generating a plausible but syntactically unfaithful interpretation. In English, ORCs are also more susceptible to these thematic role reversals (e.g., Zhou & Christianson, 2016a). Unlike the case of English relative clauses, however, plausibility and structure did not interact in the current Chinese relative clauses in online or offline measures.…”
Section: Plausibilitymentioning
confidence: 97%
See 3 more Smart Citations